2009
DOI: 10.1186/1471-2458-9-471
|View full text |Cite
|
Sign up to set email alerts
|

Remaining life expectancy among older people in a rural area of Vietnam: trends and socioeconomic inequalities during a period of multiple transitions

Abstract: BackgroundBetter understanding of the trends and disparities in health at old age in terms of life expectancy will help to provide appropriate responses to the growing needs of health and social care for the older population in the context of limited resources. As a result of rapid economic, demographic and epidemiological changes, the number of people aged 60 and over in Vietnam is increasing rapidly, from 6.7% in 1979 to 9.2% in 2006. Life expectancy at birth has increased but not much are known about change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 30 publications
0
38
1
Order By: Relevance
“…The mMajor products are wet rice, cassava, corn, soya beans, green beans and fruits such as pineapple, mandarin orange and papaya. Other economic activities are forestry (8%), fishing (1%), small trade (3%), handicraft (6%) and transport (1%) [12,15]. …”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The mMajor products are wet rice, cassava, corn, soya beans, green beans and fruits such as pineapple, mandarin orange and papaya. Other economic activities are forestry (8%), fishing (1%), small trade (3%), handicraft (6%) and transport (1%) [12,15]. …”
Section: Materials and Methodologymentioning
confidence: 99%
“…The poor is a high-risk group of people in many aspects in the society, including health and healthcare. Several studies indicate that the gap between the rich and the poor is large in healthcare spending and utilization, and that the higher socioeconomic status is correlated with better health and longer life [12-14]; however, little is known about how people use healthcare services when their economic condition changes year by year.…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic differences were significantly related to both life expectancy [13,14] and total healthy life years in the elderly [15]. Sugiura et al [16] reported that socioeconomic status accounted for a rapid increase in Japanese life expectancy after the Second World War.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence [3] that life expectancy at age 60 increased overall in rural areas, but decreased among the most vulnerable groups such as older women living without children or grandchildren. Poverty status and living arrangements lead to a wide gap in life expectancy.…”
Section: Introductionmentioning
confidence: 99%